Exenatide for obesity in children and adolescents: Systematic review and meta-analysis - Chen, Bin; Zou, Zhuan; Zhang, Xiaoyan; Xiao, Dongqiong; Li, Xihong (Frontiers in Pharmacology, 2024)
Objectives: There is no curative treatment for childhood obesity. We aim to synthesize published Randomized Controlled Trials (RCTs) evidence on the efficacy of exenatide in obese children and adolescents.We conducted a comprehensive search and analysis of relevant studies in popular databases such as PubMed, Web of Science, Embase, and Cochrane Library.Our focus was on RCTs that examined the effectiveness of exenatide for treating obesity in children. We primarily assessed changes in body weight, body mass index (BMI), fasting plasma glucose (FPG), or HbA1c levels. Additionally, we considered any adverse events reported during the treatment period, with particular attention to hypoglycemia. To evaluate the quality of RCTs included in our study, we employed the Cochrane bias assessment tool.Results: Five studies met the inclusion criteria. A group of 100 children were assigned to receive treatment with exenatide. Compared with controls, exenatide therapy reduced body weight and BMI by -0.6% (95% CI -0.93, -0.27), -1.11% (95% CI -1.91, -0.31), respectively. Undesirable consequences encompass gastrointestinal symptoms, with the majority of instances being characterized by mild severity.Exenatide demonstrates efficacy in the treatment of pediatric and adolescent obesity.